Attitudes of the Postgraduate Students of Manipur University towards Entrepreneurship - Meinam, Martina; Nath Ojha, Sekhar; Shanmugam Ananthan, Pachampalayam; Sharma, Arpita; Meinam, Teresa; Jackie Singh, Yumlembam; Mir, Shakir Ahmad (Indian Journal of Extension Education, 2023)
The attitudes of the student were studied using affective, behavioural, and cognitive components during 2020-2021 among the postgraduate students of Manipur University (MU). A structured interview schedule was used and data were collected from 160 respondents using stratified random sampling from five Schools of Studies of the university. Entrepreneurship Attitudes Score of students was found to be ‘0.647’ for the School of Humanities; ‘0.635’ for the School of Human & Environmental Sciences, ‘0.702’ for the School of Social Sciences, ‘0.609’ for the School of Life Sciences; ‘0.677’ for the School of Mathematical and Physical Sciences. The overall score of students’ attitudes towards entrepreneurship was found to be 0.65, revealing that the majority of the students (58.28%) were moderately favourable towards entrepreneurship. Kruskal-Wallis test was used and found that students of the School of Social Sciences and male students showed higher attitude towards entrepreneurship; 44.14% of the students showed highly favourable towards entrepreneurship. School of Social Science students were found to be more aware of the potential resource and were more aware of different programmers, schemes, ideas and strategies. Such potent and knowledgeable students should be selected and nurtured with proper training, exposure and making them aware of different Government schemes.